PENYULUHAN DAN PENANGANAN FISIOTERAPI PADA OSTEOARTHRITIS BILATERAL MENGGUNAKAN INTERVENSI ISOMETRIC EXERCISE DI KOMUNITAS KELUARGA DESA PASEKARAN BATANG - Nur Susanti; Puji Wahyuningrum (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
Geriatric or elderly people usually experience physiological changes in the form of sagging skin and facial wrinkles and persistent lines, head hair turns white or gray, teeth begin to loose (toothless), vision and hearing loss, easily tired and fall easily, movement becomes sluggish and less agile. The problem experienced by the elderly is knee pain. Osteoarthritis is a degenerative disease of the joints characterized by pathological symptoms in the entire joint structure, damage to joint cartilage, the appearance of sclerosis and osteophytes at the edges of the bones, stretching of the joint capsule, inflammation and weakness of the muscles around the joints. From the observation process of identifying physiotherapy problems in the elderly by lecturers and D III students of the Department of Physiotherapy, Faculty of Health, Pekalongan University, which was carried out by interviewing family members, it was found that the problem most often complained of was knee pain. The situation analysis is in the form of observations made by students in the family community of Pasekaran Batang Village. solution offered that is by using the isometric exercise modality and physiotherapy treatment for osteoarthritis.The purpose of this activity is to increase knowledge and understanding to the elderly about the role of physiotherapy in the elderly, especially in the management of knee pain. The implementations before the process of counseling and handling the elderly, a pre-test and a post-test are given, which make the benchmarks for the elderly's understanding of what treatments can be done for knee pain. the results of the pre-test and post-test proved that the level of understanding of the elderly increased after being given counseling. It can be concluded that after being given counseling and physiotherapy treatment, the elderly's understanding of knee pain has increased. Keywords: Fisioterapi, Geriatric, Osteoarthritis, Isometric Exercise.